Growth and yield response of lettuce (Lactuca sativa L.) planted floatingly to optimization of NPK compound fertilizer - Delly Salsabila Amanda; Rahmat Hidayatulah; Susilawati Susilawati (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2025)
Urban agriculture had expanded rapidly in response to growing population pressures and climate change, especially in densely populated areas of developed countries. South Sumatra holds significant potential for developing floating agricultural systems. This study aimed to evaluate the effects of compound NPK fertilizer and a floating planting system on lettuce growth. A Randomized Block Design (RBD) with four treatment levels was used. Each treatment was repeated 3 times, resulting in 12 treatment units. In the treatment of NPK compound fertilizer doses, P0 = Control, P1 = 1.12 g NPK compound/polybag, P2 = 2.24 g NPK compound/polybag, P3 = 3.36 g NPK compound/polybag. The observation results were analyzed using analysis of variance and the DMRT 5% test. The parameters observed include plant height, number of leaves, fresh weight of the plant, fresh weight of the roots, dry weight of the roots, root length, leaf greenness level, leaf area, and canopy area. Based on the research findings, the application of compound NPK fertilizer at a rate of 2.24 g/polybag (P2) resulted in the most favorable growth and yield performance of floating lettuce, as it consistently produced the highest mean values across all observed parameters. However, the calculated optimum dosage was 2.05 g/polybag. This rate is therefore recommended as the optimal application dose for subsequent studies.